MANAGEMENT ACCOUNTING, INNOVATIVE ECONOMY, MANAGEMENT - K.M. Balginova; A.A. Zhalgasbayev; M.G. Kairgalieva (Academic Journal of Physical and Chemical Sciences, 2019)
In conditions of high complexity and uncertainty of the business environment, the information generated in management accounting is the basis for managers to make rational management decisions. The conditions of an innovation-oriented market economy are changing the traditional idea of management accounting and require the development of its separate areas in enterprises in order to generate information sufficient for effective innovation management, analysis of customer preferences of customers in innovative products and proper monitoring of the implementation of innovative projects. Therefore, in the course of the study it was determined that one of the important areas of development of management accounting is management accounting of innovations. Management accounting of innovations includes not only accounting as such, but also an analysis of the innovative environment and innovative potential of the enterprise, the formulation of innovative goals and objectives of the enterprise, monitoring the achievement of innovative goals, which are described in more detail in this study by the authors of the article.